High-Fat Diet-Induced Renal Proximal Tubular Inflammatory Injury: Emerging Risk Factor of Chronic Kidney Disease - Chen, Shuxian; Chen, Jinxia; Li, Shangmei; Guo, Fengbiao; Li, Aifen; Wu, Han; Chen, Jiaxuan; Pan, Quanren; Liao, Shuzhen; Liu, Hua-feng; Pan, Qingjun (Frontiers in Physiology, 2021)
Nowadays, with the improvements in living standards and changes in living habits, high fat diet (HFD) has become much more common in the populations worldwide. Recent studies have shown that HFD could induce lipid accumulation, and structural and functional abnormalities, accompanied by the release of large amounts of pro-inflammatory cytokines, in proximal tubular epithelial cells (PTECs). These findings indicate that, as an emerging risk factor, PTEC injury induced by HFD may be closely related to inflammation; however, the potential mechanisms underlying this phenomenon is still not well known, but may involve the several inflammatory pathways, including the myeloid differentiation factor 2/Toll like receptor 4 (MD2/TLR4) signaling pathway, the kidney injury molecule 1 (KIM-1)-related pathway, the non-coding RNA (ncRNA) regulatory system, a defective fatty acid oxidation (FAO) system, and nuclear factor-κB (NF–κB) activation, etc., and the detailed molecular mechanisms underlying these pathways still need further investigated in the future. Based on lipid abnormalities-induced inflammation is closely related to the development and progression of chronic kidney disease (CKD), to summarize the potential mechanisms underlying HFD-induced renal proximal tubular inflammatory injury, may provide novel approaches for CKD treatment.